2019
DOI: 10.1088/1361-648x/ab36e5
|View full text |Cite
|
Sign up to set email alerts
|

Stress- and electric-field-induced band gap tuning in hexagonal boron phosphide layers

Abstract: Two-dimensional hexagonal boron phosphide presents great potential in applications of electronics and optoelectronics due to its high carrier mobility and moderate band gap. In this work, we investigate the effect of stress and electric field on the electronic properties of hexagonal boron phosphide layers based on first-principles calculations. We find that both the band gap and the carrier effective masses of hexagonal boron phosphide monolayer gradually increase with stress from compression to tension. As f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…Therefore, there have been some studies on bilayer BP, and Chen et al 25 have shown that the most stable bilayer BP stacks have direct band gaps and exhibit a significant Stark effect in the presence of E > . Furthermore, Wang et al 26 found that the band gap of bilayer BP is 1.098-1.312 eV, and its effective mass is approximately about times the rest mass of an electron (m 0 ). Therefore, it has promising applications in the field of photoelectricity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there have been some studies on bilayer BP, and Chen et al 25 have shown that the most stable bilayer BP stacks have direct band gaps and exhibit a significant Stark effect in the presence of E > . Furthermore, Wang et al 26 found that the band gap of bilayer BP is 1.098-1.312 eV, and its effective mass is approximately about times the rest mass of an electron (m 0 ). Therefore, it has promising applications in the field of photoelectricity.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] However, few studies have focused on its optical properties, and the strain modulation effects are not sufficiently studied. 12 It is thus our motivation to systematically research the electronic structure and optical properties of h-BP monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, single-layer boron phosphide (BP) has been successfully synthesized on sapphire or silicon substrates 14,15 and its properties predicted using different theoretical calculations. 16,17 It is obvious that single-layer BP is a semiconductor with a direct band gap of about 1.0-2.0 eV, depending on the measurement approaches. 18,19 Single-layer BP shows high carrier mobilities (over 10 4 cm 2 V À1 s À1 ), 20 which are comparable with those in graphene (10 5 cm 2 V À1 s À1 ).…”
Section: Introductionmentioning
confidence: 99%